On the development of the chondrocranium and the histological anatomy of the head in perinatal stages of marsupial mammals. Issue 1 (December 2017) - Sánchez-Villagra, Marcelo; Forasiepi, Analía
Abstract An overview of the literature on the chondrocranium of marsupial mammals reveals a relative conservatism in shape and structures. We document the histological cranial anatomy of individuals representingMonodelphis domestica, Dromiciops gliroides, Perameles sp. andMacropus eugenii . The marsupial chondrocranium is generally characterized by the great breadth of the lamina basalis, absence of pila metoptica and large otic capsules. Its most anterior portion (cupula nasi anterior) is robust, and anterior to it there are well-developed tactile sensory structures, functionally important in the neonate. Investigations of ossification centers at and around the nasal septum are needed to trace the presence of certain bones (e.g., mesethmoid, parasphenoid) across marsupial taxa. In many adult marsupials, the tympanic floor is formed by at least three bones: alisphenoid (alisphenoid tympanic process), ectotympanic and petrosal (rostral and caudal tympanic processes); the squamosal also contributes in some diprotodontians. The presence of an entotympanic in marsupials has not been convincingly demonstrated. The tubal element surrounding the auditory tube in most marsupials is fibrous connective tissue rather than cartilage; the latter is the case in most placentals recorded to date. However, we detected fibrocartilage in a late juvenile ofDromiciops, and a similar tissue has been reported forTarsipes . Contradictory reports on the presence of the tegmen tympani can be found in the literature. We describe a small tegmen tympani inMacropus . Several heterochronic shifts in the timing of development of the chondocranium and associated structures (e.g., nerves, muscles) and in the ossification sequence have been interpreted as largely being influenced by functional requirements related to the altriciality of the newborn marsupial during early postnatal life. Comparative studies of chondocranial development of mammals can benefit from a solid phylogenetic framework, research on non-classical model organisms, and integration with imaging and sectional data derived from computer-tomography.